Genetic diversity of Plasmodium vivax revealed by the merozoite surface protein-1 icb5-6 fragment - Wei Ruan; Ling-ling Zhang; Yan Feng; Xuan Zhang; Hua-liang Chen; Qiao-yi Lu; Li-nong Yao; Wei Hu (BMC, 2017)
Abstract Background Plasmodium vivax remains a potential cause of morbidity and mortality for people living in its endemic areas. Understanding the genetic diversity of P. vivax from different regions is valuable for studying population dynamics and tracing the origins of parasites. The PvMSP-1 gene is highly polymorphic and has been used as a marker in many P. vivax population studies. The aim of this study was to investigate the genetic diversity of the PvMSP-1 gene icb5-6 fragment and to provide more genetic polymorphism data for further studies on P. vivax population structure and tracking of the origin of clinical cases. Methods Nested PCR and sequencing of the PvMSP-1 icb5-6 marker were performed to obtain the nucleotide sequences of 95 P. vivax isolates collected from Zhejiang province, China. To investigate the genetic diversity of PvMSP-1, the 95 nucleotide sequences of the PvMSP-1 icb5-6 fragment were genotyped and analyzed using DnaSP v5, MEGA software. Results The 95 P. vivax isolates collected from Zhejiang province were either indigenous cases or imported cases from different regions around the world. A total of 95 sequences ranging from 390 to 460 bp were obtained. The 95 sequences were genotyped into four allele-types (Sal I, Belem, R-III and R-IV) and 17 unique haplotypes. R-III and Sal I were the predominant allele-types. The haplotype diversity (Hd) and nucleotide diversity (Pi) were estimated to be 0.729 and 0.062, indicating that the PvMSP-1 icb5-6 fragment had the highest level of polymorphism due to frequent recombination processes and single nucleotide polymorphism. The values of dN/dS and Tajima's D both suggested neutral selection for the PvMSP-1icb5-6 fragment. In addition, a rare recombinant style of R-IV type was identified. Conclusions This study presented high genetic diversity in the PvMSP-1 marker among P. vivax strains from around the world. The genetic data is valuable for expanding the polymorphism information on P. vivax, which could be helpful for further study on population dynamics and tracking the origin of P. vivax.